Dayside cosmic noise absorption at the equatorward boundary of auroral oval as observed from Maitri, Antarctica (L=5; CGM 62.45°S, 55.45°E) - Behera, Jayanta K.; Sinha, Ashwini K.; Vichare, Geeta; Kozyreva, Olga; Rawat, Rahul; Dhar, Ajay (My University, 2016)
On 02 April 2011, a couple of cosmic noise absorption (CNA) events were detected at Maitri, Antarctica (L = 5; CGM 63.14°S, 53.69°E) confining to nighttime and daytime. One of the two events that occurred during night hours was caused due to auroral substorm onset. The current study focuses on the later CNA event, which was recorded during daytime (10:00–13:00 magnetic local time (MLT), MLT = UT-1, at Maitri, Antarctica). We refer to this CNA event as dayside CNA (DCNA) event. Absence of westward electrojet during DCNA confirms its dissimilarity from auroral substorm absorption events. A comparison has been made between the DCNA event of 02 April 2011 with that of 14 July 2011, a day with substorm activity when Maitri is in dayside but without DCNA event. The comparison has been made in the light of interplanetary conditions, imaging riometer data, ground magnetic signatures, GOES electron flux density, and associated pulsations. The study shows that stronger prolonged eastward interplanetary electric field favors the occurrence of DCNA event. It is concluded that DCNA event is due to the gradient curvature drift of trapped nonrelativistic electrons in the equatorial plane. Estimated energy of trapped electrons using azimuthal drift time for a set of ground stations within the auroral oval confirms the enhancement in electron fluxes in the same energy band as recorded by geostationary satellites GOES 13 and GOES 15. The reason for precipitation of electrons is expected to be the loss cone scattering caused by wave-particle interaction triggered by ULF waves.
Keywords: Antarctica; Maitri; Cosmic noise absorption; CNA; Auroral substorm; DCNA; Geostationary satellites; GOES 13